1998
DOI: 10.1021/jp981899y
|View full text |Cite
|
Sign up to set email alerts
|

Is a Transition State Planar or Nonplanar in Oxidative Additions of C−H, Si−H, C−C, and Si−C σ-Bonds to Pt(PH3)2? A Theoretical Study

Abstract: A theoretical study of oxidative additions of H−CH3, CH3−CH3, H−SiR3, and SiR3−CH3 (RH, Cl, or Me) to Pt(PH3)2 was carried out with ab initio MO/MP2-MP4SDQ, CCD, and CCSD methods. The oxidative addition reactions of C−H and Si−H σ-bonds occur through a planar transition state (TS) structure, in accordance with the expectation from an orbital interaction diagram. However, the oxidative addition reactions of CH3−CH3 and SiH3−CH3 take place through a nonplanar TS structure, unexpectedly; the dihedral angle δ bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
54
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 58 publications
13
54
0
Order By: Relevance
“…The dihedral angles (d) between the Pt-P-X (X: midpoint of CBC) and Pt-Si-C1 planes in Fig. 3 indicate that the TS geometries for R ¼ Me and Pr are distorted similar to the one previously reported for Pt(PH 3 ) 2 (CH 3 )(SiH 3 ) [13]. The distortion was ascribed to steric repulsion between the CH 3 -SiH 3 and PH 3 groups.…”
Section: P2supporting
confidence: 69%
“…The dihedral angles (d) between the Pt-P-X (X: midpoint of CBC) and Pt-Si-C1 planes in Fig. 3 indicate that the TS geometries for R ¼ Me and Pr are distorted similar to the one previously reported for Pt(PH 3 ) 2 (CH 3 )(SiH 3 ) [13]. The distortion was ascribed to steric repulsion between the CH 3 -SiH 3 and PH 3 groups.…”
Section: P2supporting
confidence: 69%
“…515b Sakaki and co-workers addressed the transition state on OA of Si-H and of Si-C (and the corresponding carbon compounds) to Pt(PH 3 ) 2 (with a linear P-Pt-P geometry) by ab initio methods (MO/MP2-MP4SDQ, CCD, and CCSD). 511 These calculations revealed that the OA of Si-H σ-bonds occurred through a planar TS that was predicted from the orbital interaction diagram, but the OA of SiH 3 CH 3 took place through an unexpected nonplanar TS. The interesting feature for OA of Si-C was that the Si-C approached parallel to the P-Pt-P axis, and as the Si-C lengthens, the Si-C bond pivoted and became approximately perpendicular to the PtP 2 plane.…”
Section: Nickel Triadmentioning
confidence: 79%
“…The whole mechanism could be described in three main steps [2,23]: (a) oxidative addition, (b) transmetalation, and (c) reductive elimination. Contrary to steps (a) and (c), that have been the subject of several experimental [24][25][26][27][28][29][30] and theoretical [31][32][33][34][35][36][37][38][39][40] studies less is known about the transmetalation process [41][42][43][44][45][46][47][48][49][50]. This is thus the most characteristic step of the cross-coupling reactions.…”
Section: Introductionmentioning
confidence: 99%